2018
DOI: 10.2135/cropsci2017.08.0513
|View full text |Cite
|
Sign up to set email alerts
|

Spacing Effect on Energy Cane Growth, Physiology, and Biomass Yield

Abstract: Energy cane is a specialized sugarcane (Sacharum spontaneum L.) hybrid developed for high lignocellulosic biomass for biofuel production. The optimum planting spacing for energy cane is not known; hence, it has been planted with sugarcane planting spacing. We examined the effect of six plant spacings derived from three inter‐ (1.22, 1.52, and 1.83 m) and two intra‐row (0.61 and 0.91 m) spacings on energy cane growth, physiology, and biomass yield. Energy cane was planted in fall 2012, was harvested after estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
4
12
1
Order By: Relevance
“…In this study, napiergrass showed tremendous ability to regrowth, even after its harvest in October when day/night temperatures had dropped considerably compared with those in the summer. Reduced photosynthesis under low temperature in perennial grasses and other crops have been reported in previous studies (Chiluwal, 2018;Chiluwal et al, 2018aChiluwal et al, , 2018b. Hence, vigorous regrowth observed in this experiment cannot be explained by ongoing photosynthesis, as the temperature regime during the regrowth period was not optimum for plants to photosynthesize at the highest rates, and the day length had shortened due to the fall season.…”
Section: Treatmentsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, napiergrass showed tremendous ability to regrowth, even after its harvest in October when day/night temperatures had dropped considerably compared with those in the summer. Reduced photosynthesis under low temperature in perennial grasses and other crops have been reported in previous studies (Chiluwal, 2018;Chiluwal et al, 2018aChiluwal et al, , 2018b. Hence, vigorous regrowth observed in this experiment cannot be explained by ongoing photosynthesis, as the temperature regime during the regrowth period was not optimum for plants to photosynthesize at the highest rates, and the day length had shortened due to the fall season.…”
Section: Treatmentsupporting
confidence: 70%
“…Biomass yield obtained from napiergrass in this study was much higher than other energy crops types such as switchgrass, miscanthus, sorghum [Sorghum bicolor (L.) Moench], and energy cane (Saccharum hyb.) (Arundale et al, 2014;Haines et al, 2015;Chiluwal et al, 2018b;Sainju et al, 2018aSainju et al, , 2018b, and hence provide further evidence that napiergrass could be one of the potential lignocellulosic feedstocks in Georgia and other areas with similar climatic conditions.…”
Section: Discussionmentioning
confidence: 67%
“…As only one time point was sampled in that study, the detected differences in expression levels could be an indication of the phase differences we detected (Supplemental Figure S9). When row spacings in sugarcane fields were changed between 1.5 m and 2.3 m, cane yields (t/ha) were maintained, as the stalk numbers and weight would change in response to different plant densities (Garside et al, 2009;Chiluwal et al, 2018). In grapes,…”
Section: Resultsmentioning
confidence: 99%
“…When row spacings in sugarcane fields were changed between 1.5 m and 2.3 m, cane yields (t/ha) were maintained, as the stalk numbers and weight would change in response to different plant densities (Garside et al, 2009;Chiluwal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In case of first and second ratoons, stalk population varied from 10 to 30 and 10 to 15 stalks m −2 , respectively. In an energy cane study conducted in Georgia, Chiluwal et al (2018) both plant cane and first ratoon. The stalk population of plant cane recorded in our study was similar to these previously reported studies.…”
Section: Stalk Populationmentioning
confidence: 99%